Surgery of Left Temporal Region Arachnoid Cyst with Neuroendoscopy: A Case Report - Wiwoho, Yudi Yuwono; Rolian, Danu; Ichwan, Syaiful; Mulyawan, Wawan (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction: Today, the development of minimally invasive neurosurgery technique, has become a choice of treatment for many neurosurgical disease. Dr.Suyoto Hospital, Rehabilitation Center, Ministry of Defence of the Republic of Indonesia and Indonesian Airforce Hospital Dr. Esnawan Antariksa, Halim Perdanakusuma, Jakarta, Indonesia, has responsibility in public health services for military and civilian community. This paper has an objective to share experience in giving treatment with intracranial neuroendoscopy technique for patient with left temporal region arachnoid cyst. Case Report: Case Report 1 : Girl, 17 years old, with headache. There was no neurological deficit, and from brain CT Scan, there was a cystic lesion at the left temporal region. The diagnosis was arachnoid cyst. She performed neuroendoscopic cystotomy and insertion of Omaya reservoir. After surgery, she had no headache, and there were no post-operative complications. Histopatology finding was arachnoid cyst. From follow up of brain CT Scan, there was improvement. We used intracranial neuroendoscopy device from B-Braun Aesculap, Germany, 2015. Case Report 2 : Boy, 8 years old, with seizure and headache. There was no neurological deficit, and from brain CT Scan, there was a cystic lesion at the left temporal region. The diagnosis was arachnoid cyst. He performed neuroendoscopic cystotomy and insertion of Omaya reservoir. Dicussion: After surgery, he had no headache and also had no seizure, and there were no post-operative complications. Histopatology finding was arachnoid cyst. From follow up of brain CT Scan, there was improvement. We used intracranial neuroendoscopy device from B-Braun Aesculap, Germany, 2015. Conclusion: Intracranial neuroendoscopy technique can be applied for the treatment of many special and selective neurosurgical diseases, including arachnoid cyst. In this patient, intracranial neuroendoscopy had good result. We still need more many of cases for determine the success rate of this intracranial neuroendoscopy technique statistically